Analisis Pemilihan Rute dengan Logika Fuzzy - Atikah Kartika; Nahdalina Nahdalina (Jurnal Teknik Sipil, 2023)
Travelers have different perceptions in determining the direction of the travel route. The purpose of this study is to predict route selection based on the fastest route by considering the variables of travel time, average speed, and the degree of road saturation. The method used consists of a combination of route selection and route weighting. The weighting of the route is calculated using the fuzzy logic of the Mamdani method by producing the lowest weight. The research was conducted in Bogor Regency with 1 origin and 3 destinations connected by 25 roads and 19 node points. The analysis carried out consists of 2 scenarios. The results of the analysis show that the routes generated based on scenario 1 and scenario 2 are different. The results of scenario 1 use the travel time and DS for origin 1 to destination 2 via node 1-10-11-7-5-6-9-2 with a weighting value of 0.186, origin 1 to destination 3 via node 1-10-12- 13-14-3 with a weighting result of 0.224, and from 1 to destination 4 via node 1-10-12-15-16-18-19-4 with a weighting result of 0.291. While the results of scenario 2 average speed and DS for origin 1 to destination 2 through node 1-10-11-7-8-9-2 with a weighting result of 0.198, origin 1 to destination 3 goes through node 1-5-6-9- 8-13-14-3 with a weighting result of 0.222, and from 1 to destination 4 through node 1-5-6-9-8-13-12-15-16-17-19-4 with a weighting result of 0.208. The program validation rate reaches 99.91%.